Incidence of Cyp51 A key mutations in Aspergillus fumigatus-a study on primary clinical samples of immunocompromised patients in the period of 1995-2013. - Birgit Spiess (Public Library of Science (PLoS), 2014)
As the incidence of azole resistance in Aspergillus fumigatus is rising and the diagnosis of invasive aspergillosis (IA) in immunocompromised patients is rarely based on positive culture yield, we screened our Aspergillus DNA sample collection for the occurrence of azole resistance mediating cyp51 A key mutations. Using two established, a modified and a novel polymerase chain reaction (PCR) assays followed by DNA sequence analysis to detect the most frequent mutations in the A. fumigatus cyp51 A gene conferring azole resistance (TR34 (tandem repeat), L98H and M220 alterations). We analyzed two itraconazole and voriconazole and two multi-azole resistant clinical isolates and screened 181 DNA aliquots derived from clinical samples (blood, bronchoalveolar lavage (BAL), biopsies, cerebrospinal fluid (CSF)) of 155 immunocompromised patients of our Aspergillus DNA sample collection, previously tested positive for Aspergillus DNA and collected between 1995 and 2013. Using a novel PCR assay for the detection of the cyp51 A 46 bp tandem repeat (TR46) directly from clinical samples, we found the alteration in a TR46/Y121F/T289A positive clinical isolate. Fifty stored DNA aliquots from clinical samples were TR46 negative. DNA sequence analysis revealed a single L98H mutation in 2010, two times the L98H alteration combined with TR34 in 2011 and 2012 and a so far unknown N90K mutation in 1998. In addition, four clinical isolates were tested positive for the TR34/L98H combination in the year 2012. We consider our assay of epidemiological relevance to detect A. fumigatus azole resistance in culture-negative clinical samples of immunocompromised patients; a prospective study is ongoing.